2021
DOI: 10.1097/jom.0000000000002353
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Mortality Among Fighter Aviators in the United States Air Force

Abstract: Objective: This study sought to clarify cancer risk in fighter aviators. Methods: US Air Force officers who served between 1970 and 2004 were followed through 2018 for incidence and mortality of 10 cancers: colon and rectum; pancreas; melanoma skin; prostate; testis; urinary bladder; kidney and renal pelvis; brain and other nervous system; thyroid; and non-Hodgkin lymphoma. Fighter aviators were compared with other officers and the general US population. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…One of our most consistent findings of elevated TGCT risk for pilots is comparable with the findings of some of the previous studies conducted among USAF servicemen,14–16 although not all 29. Previous studies that found elevated risk/odds of TGCT among aviators slightly differed with respect to the exposure metrics.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…One of our most consistent findings of elevated TGCT risk for pilots is comparable with the findings of some of the previous studies conducted among USAF servicemen,14–16 although not all 29. Previous studies that found elevated risk/odds of TGCT among aviators slightly differed with respect to the exposure metrics.…”
Section: Discussionsupporting
confidence: 89%
“…We, therefore, primarily relied on occupational information at time 2, on average 8.2 years post-accession, when approximately only 3% of the population was non-occupationally qualified. For selected occupations of interest based on prior literature (ie, pilot, fighter pilot, firefighting and aircraft maintenance),8 16 25–27 we additionally created occupational groupings that indicated being in a given occupation at both time points (eg, pilot at time 1 and at time 2, aircraft maintenance at time 1 and at time 2). We did not have information on occupation timing and duration (eg, when a serviceman started or ended a job).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Longer air hours, number of employment years, and radiation exposure positively correlate with increased PCa risk [ 19 , 67 ]. Male pilots are at least twice as likely to develop PCa than men in the general population, and several subgroups, including AA pilots and military pilots, were found to have an increased riskforf PCa [ 18 , 68 ].…”
Section: Introductionmentioning
confidence: 99%